An Assessment of Combination of the Camrelizumab With Chemotherapy in Metastatic Biliary Tract Cancers. (12th May 2021) - Yu, Yi; Huang, Shanshan; Chen, Jun; Yu, Feng; Zhang, Lin; Xiang, Xiaojun; Deng, Jun; Fang, Ziling; Li, Junhe; Xiong, Jianping
Background: Monoclonal antibodies that target the PD-1 receptor are emerging as promising therapeutic candidates for the treatment of biliary tract cancers (BTCs). The purpose of the current study was to assess the combination of the camrelizumab with chemotherapy as a first-line treatment for metastatic BTCs. Methods: We conducted a prospective single-arm pilot study of PD-1 antibody (camrelizumab 3 mg/kg d1, Q2 W or Q3 W) combined with different chemotherapy regimens as first-line treatment for BTCs. Efficacy endpoints were objective response rate (ORR), disease control rate (DCR), progression free survival (PFS), and overall survival (OS). Treatment-related adverse events (TRAEs) were also evaluated. Results: Fourteen patients with histologically confirmed BTCs were evaluated. The ORR was 14.3% (95% CI: 1.8 to 42.8) and the DCR was 64.3% (95%CI: 41.7 to 86.9). The median PFS was 6.5 months (95% CI: 3.8 to 9.2), and the 6- and 12-month PFS rates were 61.6% and 12.3%, respectively. The median OS was 9.9 months (95% CI: 7.6 to 12.2), and the 6-and 12-month OS rates were 74.5% and 26.6%, respectively. All patients displayed at least 1 TRAE., and Grade 3 or 4 TRAEs occurred in 6 (42.86%) patients. Conclusions: Camrelizumab combined with chemotherapy as first-line treatment for metastatic BTCs demonstrated acceptable safety and efficacy in our pilot study. These findings warrant prospective controlled clinical trials comparing combinations of camrelizumab and chemotherapy to standard regimens.